Analyzing mood structures in the Quranic stories of Nuh: a comparative study of Quranic translations - Otay, Areej Ali; Abdul Jabar, Mohd Azidan; Hassan, Abd Rauf; Islam, Muhd Zulkifli (Academy Publication, 2025)
To properly translate rhetorical questions, the paper addresses how to preserve and analyze thematic structures in translations of religious texts. It mainly concentrates on how translators understand and communicate the interpersonal mood structures found in the Quranic Nuh stories in the Quranic translations by Abdullah Yusuf Ali and by Muhammad Taqi-ud-Din Al-Hilali and Muhammad Muhsin Khan. Nuh's stories were chosen mainly because they provide a rich tapestry of divine pronouncements, pleas, and rhetorical inquiries and highlight how clear mood rules conversations, aiming at explaining the impact of translation choices on mood distribution and potential interpretive nuances. Employing the Systemic Functional Linguistics (SFL) framework, the study analyzes the distribution of declarative, imperative, and interrogative moods within the Nuh stories across both translations. The analysis revealed a consistent dominance of the declarative mood across the two translations, reflecting the narrative's primary focus on conveying information and pronouncements. However, significant variations emerge in the usage of imperative and interrogative moods. The study identifies translator-specific tendencies, highlighting how confident choices amplify or subdue the urgency of commands or the intensity of rhetorical questions. Furthermore, the findings show that linguistic variations exist across languages regarding how declarative is constructed. Findings also articulated the diverse subtypes that help realize emerging declarations within different translation approaches. Moreover, Nuh's stories show high imperative usage by reflecting the guidance-oriented themes. Conversely, the blend of declarative, imperatives, and interrogatives at the particular stage of Nuh's spreading Allah’s message hints at a dynamic interplay of information, instruction, and rhetorical questioning.